Assessing the challenges of managing product design change through-life. Issue 1 (3rd March 2016) - Morris, Ashley; Halpern, Marc; Setchi, Rossi; Prickett, Paul
ABSTRACT: Whole-life support for complex products requires coordinated action. Existing shortcomings of the design change management process currently operated within key UK engineering sectors are identified and discussed. The challenges that must be met in order to better satisfy the need for accurate product information across an integrated supply chain are presented. The role that information technology must play in achieving greater efficiency is developed. Recommendations are made in the form of 10 requirements to guide future design change management strategies. It is intended that implementation of these requirements will enable and improve the provision of product-related information so that it more accurately reflects the current configured status of the products. The aim is to facilitate and support enhanced product maintenance, effectiveness and utilisation.